Comprehensive NIH-Funding Analysis of Academic Cardiac Surgeons - Narahari, Adishesh K. (J Thorac Cardiovasc Surg, 2019)
OBJECTIVE: National Institutes of Health (NIH) funding is becoming increasingly difficult to obtain. We sought to determine trends in NIH funding for cardiac surgeons hypothesizing they are at a disadvantage in obtaining funding due to intensive clinical demands. METHODS: Cardiac surgeons (adult/congenital) currently at the top 141 NIH-funded institutions were identified using institutional websites. The NIH funding history for each cardiac surgeon was queried using NIH Research Portfolio Online Reporting Tools Expenditures and Results (RePORTER). Total grant funding, publications, and type was collected. Academic rank, secondary degrees, and fellowship information was collected from faculty pages. Grant productivity was calculated using a validated Grant Impact Metric. RESULTS: A total of 818 academic cardiac surgeons were identified, of which 144 surgeons obtained 293 NIH grants totaling $458 million and resulting in 6,694 publications. We identified strong associations between an institution’s overall NIH funding rank and the number of cardiac surgeons, NIH grants to cardiac surgeons, and amount of NIH funding to cardiac surgeons (all p<0.0001). The majority of NIH funding to cardiac surgeons is concentrated in the top quartile of institutions. Cardiac surgeons have high conversion rates from K-awards (mentored development award) to R01s (6/14; 42.9%). Finally, we demonstrate the rate of all NIH grants awarded to cardiac surgeons has increased, driven primarily by P and U (collaborative project) grants. CONCLUSIONS: NIH-funded cardiac surgical research has resulted in significant impact over the last three decades. Aspiring cardiac surgeon-scientists may be more successful at top quartile institutions due to infrastructure and mentorship.